Youth Political Engagement in Transitional Societies: Trends, Drivers, and Challenges - Mensah, Kwame A.; Boateng, Ama Serwaa (Emerging Perspective in Social and Politics, 2026)
Youth political engagement plays a critical role in shaping democratic development, particularly in transitional societies undergoing shifts from authoritarian rule, conflict, or major political reform. This mini review synthesizes recent literature to examine the trends, drivers, and challenges influencing youth participation in these contexts. Key trends include the increasing use of digital platforms for political mobilization, the rise of youth-led movements and grassroots activism, and a shift from traditional, party-based engagement toward issue-driven, noninstitutional forms of participation. Drivers of engagement encompass education and civic awareness, which equip youth with the knowledge and skills necessary for informed participation; digital media and information access, which enable rapid communication and advocacy; socioeconomic conditions, including unemployment and social inequality, which motivate activism; and political opportunities and institutional reforms, which create formal avenues for meaningful involvement. Despite these enabling factors, youth face persistent challenges such as political distrust, weak institutions, limited representation, legal restrictions, and risks associated with digital misinformation. Addressing these barriers is essential for enhancing the effectiveness and sustainability of youth participation. Policy implications include strengthening civic education and leadership programs, promoting inclusive political institutions, supporting safe and constructive digital engagement, and increasing youth representation in governance. The review underscores the importance of empowering youth as active agents of change to consolidate democratic processes in transitional societies. Future research is needed to evaluate the long-term impacts of youth political engagement on governance, policy reform, and social cohesion, providing evidence-based guidance for policymakers, educators, and civil society actors.